Tender is the night - Stern, Milton R. (Twayne u.a., 1994)
F. Scott Fitzgerald's Tender Is the Night may or may not be the great American novel, but it is the great novel about American History. It is also a novel about Fitzgerald's life history. In the making for nearly 10 years and the subject of 18 revisions - the last undertaken after the book was first published in 1934 - Tender Is the Night is an expression of Fitzgerald's struggle to come to terms with his increasingly dark view of post-World War I American culture and with the disintegration of his personal life. Between the years 1925 and 1934, while working intermittently on Tender Is the Night, Fitzgerald experienced the complete mental breakdown of his wife, Zelda, the death of his father, and a demoralizing encounter with the Hollywood movie industry that coupled professional diminishment with financial dependence. He also witnessed the collapse of the country's high-flown Jazz Age into the impoverishment of the Great Depression All of these events, writes Milton Stern, contributed to the profound sense of loss and disillusionment that colors the novel. The novel's two primary characters - the protagonist, idealistic psychiatrist Dick Diver, and his emotionally troubled wife, Nicole - suggest Fitzgerald's two visions of America. One, embodied in Dick, is naively attached to a false view of the past as incorruptibly good and of the future as transcendent; it is the ideal America. The other, represented by Nicole, is confused, fractured, damaged; it is the America scarred by the harsh contest for money and power characterizing the post-World War I era, the real America. As Dick and Nicole move from young to middle adulthood, Fitzgerald examines the complexities of their inner and outer worlds: the effects of war, the problems of sexual identity and sexual warfare, the nature of wealth, the struggle for moral responsibility, the human capacity for exploitation The ultimate failure of their marriage, and above all of Dick Diver to fulfill his youthful promise, leaves the reader with a deep sense of loss and a yearning nostalgia for the idea of what could have been - for Nicole, particularly for Dick, and perhaps for America. Given the current emphasis on historicist reconstructions of American literature, Stern's focus on the influence of history is timely. He rounds out his analysis with a critical examination of the novel's literary motifs, imagery, and symbols to give the reader a richly informed assessment of Fitzgerald's chronicle of a personal and national fall from grace
Keywords: Fitzgerald; F. Scott <1896-1940>; Tender is the night; Fitzgerald; F. Scott